A Black Practice that Has Won White People: Symbol, History and Devotes in the Cult of Lord of the Miracles in Lima (XIX-XXI Centuries) - Costilla, Julia (2016)
The cult of Lord of the Miracles takes place every October in Lima with an extraordinary attendance and it renovates on the practice of thousands of devotes around the world. Within a larger study of the history of this symbol from XVII century, I will follow him from his colonial institutionalization (1771) to his republican trajectory in order to explore how his mayor meanings were made up: a mestizanational identity and an afrodescendent tradition. Methodologically, I will use the approach of historic anthropology, with ethnographic and archive sources and with an anthropological-historical point of view. In this way, I will demonstrate how the cult definition as “black practice that has won white people” can summarize the itinerary of that symbol on two levels: in terms of his tricentenary historical process and in terms of representations about that process.